2019
DOI: 10.3390/mps2020046
|View full text |Cite
|
Sign up to set email alerts
|

The Optimized Workflow for Sample Preparation in LC-MS/MS-Based Urine Proteomics

Abstract: The sample condition is an important factor in urine proteomics with stability and accuracy. However, a general protocol of urine protein preparation in mass spectrometry analysis has not yet been established. Here, we proposed a workflow for optimized sample preparation based on methanol/chloroform (M/C) precipitation and in-solution trypsin digestion in LC-MS/MS-based urine proteomics. The urine proteins prepared by M/C precipitation showed around 80% of the protein recovery rate. The samples showed the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…11 and Source Data File). Such quantities are easily obtained from biological sources and the number of identifications is comparable to figures reported in the recent nano-flow LC literature [37][38][39] . In contrast to nano-flow LC, the micro-flow LC system showed no obvious sign of overloading even when injecting as much as 20 µg protein digest of non-depleted plasma protein digest, ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 53%
“…11 and Source Data File). Such quantities are easily obtained from biological sources and the number of identifications is comparable to figures reported in the recent nano-flow LC literature [37][38][39] . In contrast to nano-flow LC, the micro-flow LC system showed no obvious sign of overloading even when injecting as much as 20 µg protein digest of non-depleted plasma protein digest, ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 53%
“…The supernatant was withdrawn, and the obtained protein pellets were air-dried. The protein pellet was resuspended in sterile 8 M urea/50 mM Tris–HCl/50 mM EDTA buffer (pH 8.0), according to Saito et al ( 2019 ). The protein profile was examined for the protein integrity by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) (Laemmli 1970 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously published studies using TurboID and miniTurbo identified the depletion of free biotin after labelling as a critical step for pulldown of biotinylated proteins using streptavidin beads (Mair et al ., 2019; Zhang et al ., 2019, 2021; Arora et al ., 2020). We therefore tested three different approaches, methanol : chloroform precipitation, PD‐10 gravity column desalting and Zeba spin column desalting, to remove excess free biotin from M. polymorpha cell extracts (Mair et al ., 2019; Saito et al ., 2019; Zhang et al ., 2019). Among these three methods, the methanol : chloroform precipitation approach has not been tested for free biotin depletion from plant materials.…”
Section: Resultsmentioning
confidence: 99%